Current Status of Nonsteroidal Anti-Inflammatory Drugs in Colorectal Cancer Prevention - Petros, C. Papagiorgis (Journal of Colon And Rectal Cancer, 2015)
This review synthesizes evidence on NSAIDs and colorectal cancer prevention. It balances chemopreventive efficacy against gastrointestinal and cardiovascular risks, and considers selective COX‑2 inhibitors, dosing, and candidate populations for risk‑benefit.
Keywords: NSAID; colorectal cancer; chemoprevention; epidemiology; molecular targets